Physicians' desk reference 2017. (Montvale, NJ : PDR, LLC, 2016)
This reference contains FDA-approved drug label information, including warnings and precautions, drug interactions, and full-color images of some drugs. Every label includes information on dosages, side effects, and safety information, such as contraindications, pregnancy ratings, and interactions with other drugs, food, or alcohol.
Manufacturer's index -- Brand and generic name index -- Product category index -- Brand and generic name index for drug summaries -- Product category index for drug summaries -- Product identification guide -- Product information -- Dietary supplements -- Drug summaries -- Specialty drug summaries.
At head of title: PDR 2017 71 edition.
Includes indexes (Manufacturer's index ([1]-4 p.), Brand and generic name index ([101]-106 p.), Product category index ([201]-204 p.)).
Keywords: Drugs -- Dictionaries; Pharmacology -- Dictionaries; Catalogs, Drug; Biological Factors; Pharmaceutical Preparations; Drugs; Pharmacology; Drugs. -- Dictionaries; United States; Dictionaries